Respuesta :

For this case we have the following equation:

[tex] a ^ 2 + b ^ 2-2abcosC = c ^ 2
[/tex]

To find the value of 2abcosC we must follow the following steps:

Subtract a ^ 2 on both sides of the equation:

[tex] -a ^ 2 + a ^ 2 + b ^ 2-2abcosC = c ^ 2-a ^ 2

b ^ 2-2abcosC = c ^ 2-a ^ 2
[/tex]

Subtract b ^ 2 on both sides of the equation:

[tex] -b ^ 2 + b ^ 2-2abcosC = c ^ 2-a ^ 2-b ^ 2

-2abcosC = c ^ 2-a ^ 2-b ^ 2
[/tex]

Multiply both sides of the equation by -1:

[tex] (-2abcosC) (- 1) = (c ^ 2-a ^ 2-b ^ 2) (- 1)

2abcosC = -c ^ 2 + a ^ 2 + b ^ 2
[/tex]

Answer:

the value of 2abcosC is:

[tex] 2abcosC = -c ^ 2 + a ^ 2 + b ^ 2 [/tex]

Answer:

The value of  [tex]2ab\cos C[/tex] is  [tex]a^2+b^2-c^2[/tex]

Step-by-step explanation:

 Given : The laws of cosine is [tex]a^2+b^2-2ab\cos C=c^2[/tex]

We have to find the value of  [tex]2ab\cos C[/tex]

Consider the given formula for laws of cosine,

[tex]a^2+b^2-2ab\cos C=c^2[/tex]

Subtract both side [tex]c^2[/tex], we have,

[tex]a^2+b^2-2ab\cos C-c^2=0[/tex]

Add  [tex]2ab\cos C[/tex] both side, we have,

[tex]a^2+b^2-c^2=2ab\cos C[/tex]

Thus,  The value of  [tex]2ab\cos C[/tex] is  [tex]a^2+b^2-c^2[/tex]

ACCESS MORE